B16 Astrocytes derived from patient specific human pluripotent stem cells: a valuable biological resource for target identification in hd?. (September 2018) - Bigarreau, Julie; Baldo, Barbara; Tournois, Johana; Louessard, Morgane; Jarrige, Margot; Bonvento, Gilles; Michael, Marie; Mahé, Gurvan; Petersén, Asa; Kirik, Deniz; Perrier, Anselme L
Abstract : Several studies have outlined a non-cell-autonomous contribution in Huntington Disease (HD). Mutant-HTT (mut-HTT) expressed solely in astrocytes is sufficient for recapitulating the neurological and peripheral symptoms of HD in mice. Our objective is to identify molecules that can rescue cellular dysfunctions mediated by mut-HTT in astrocytes derived from human pluripotent stem cells (hPSC). Herein, we describe a scalable and reproducible protocol to differentiate HD-hPSC into astrocytes. The cellular identity of these hPSC-derived glial cells was characterized by qPCR and immunocytochemistry (GFAP, S100B, Connexin-43, GLT-1). Astrocytes are the cell type primarily responsible for rapid removal of glutamate from the extracellular space. This process is required for the survival and normal function of neurons. We therefore measure the capacity of the hPSC-derived glial cells we generated to glutamate uptake in a sodium-dependent manner. Assessment of previously described dysfunctions in HD-hPSC-derived astrocytes is ongoing. Next, we addressed the issue of the quantification in HD-hPSC neural derivatives of the level of mut-HTT. We adapted a mut-HTT-targeting AlphaLISA assay for use in 384-well plate format for high throughput screening. This assay is CAG dependent and can measure mut-HTT in a broad variety of human samples. We demonstrated the specificity of this assay using allele-specific silencing of the mut-HTT (lentivirus and siRNA) and comparing WT and HD-hPSC-derived samples. This assay displays a good signal-to-background ratio and is sensitive enough to reliably detect mut in as few as 5000 HD cells. The feasibility of performing drug screening on neuronal or glial cells derived from HD-hPSC using this assay is currently tested.